Automatic meteorological observation system (software design) / Abdul Rahman Mohamad Ali - Mohamad Ali, Abdul Rahman (1994)
Automatic Meteorological Observation System is a method to collect data for weather study, This system is developed based on sensing technique to be stored in data acquisition system and transmitted to central control unit which is PC based via telephone line. Measurements of the atmospheric structure functions is accomplished from atmospheric sensors situated on mini tower located at a remote area. The tower instrumentation system is microprocessor controlled which includes rain gauge, anemometer, albedometer, barometric pressure transmitter, humidity and temperature probe. The requirement of a weather data acquisition system is the conversion of the physical variables from analog to digital parameter. The data is stored into RAM storage. The remote PC controlled is used for software development. Once the task has been programmed, the computer may execute the system to display the relevant data when required,